STUDENTS’ MOTIVATION AND ATTITUDES TOWARD LEARNING ENGLISH IN AN ENGLISH COURSE - Adila Jefiza (VISION, 2017)
Most students have learned English since elementary school. However, after learning English for many years their English skills are still less than satisfactory. Well .. Why does it happen? There are several possibilities where they feel no importance of English. Some of them also only learn English to meet the demands of the task and get the value. Therefore, this study tries to investigate students' motivation in learning English, especially intrinsic and extrinsic motivation. This research was conducted with questionnaire and interview. Participants are a number of students at a course. The results of this study prove that most students have more extrinsic motivation than intrinsic and they also have a positive attitude in learning English.